WESSELS, Johannes Inventory of documents - WESSELS, Johannes (ARCA, 2018)
Private papers of J. Wessels, Managing Director Blomanda Housing Scheme; Author of several publications
COVERAGE 1961-1980; 6 Files; 0,20 Metre
Keywords: WESSELS, Johannes; Inventories